TAMI-09. ENERGY METABOLISM AND THERAPEUTIC T CELL EFFICACY IN THE GLIOBLASTOMA MICROENVIRONMENT. (9th November 2020) - Logun, Meghan; Colonna, Maxwell; Edison, Arthur; Karumbaiah, Lohitash
Abstract: Glioblastoma (GBM), like most cancers, undergo metabolic alterations to primarily utilize aerobic glycolysis in the hypoxic tumor microenvironment (TME). Similarly, activated T cells switch to glycolysis upon antigen recognition to cope with proliferation needs but are not equally equipped to survive in the hypoxic TME. Metabolic reprogramming within GBM TME contributes to therapeutic resistance and tumor progression, but the effects of metabolic alterations on therapeutic T cell survival and efficacy have not been fully elucidated. We hypothesized that hypoxia in GBM/T-cell co-cultures will significantly impair T cell proliferation and function. We conducted in vitro co-culture assays and nuclear magnetic resonance (NMR)–based assessments in hypoxic (1%O2 ) or normoxic conditions to detect metabolic changes in real-time. Imaging cytometry for cell cycle assessment demonstrated that GSCs were unaffected by hypoxia, but roughly 90% of healthy T cells arrested in G0/G1 along with significant reduction in glycan precursor UDP-GlcNAc presence. Media samples over 96h in normal and hypoxic oxygen conditions from cells in solitary or co-cultures were analyzed using a Bruker Avance III HD spectrometer at 600 MHz for comparison over time using PCA analysis of metabolic intermediate differences. After 16h, there was observable differences in produced metabolites between the T cells cultured alone or co-culture with GSCs, compared to the GSCs alone or media alone controls. Quantifiable changes in glucose, lactate, fumarate, acetate and pyruvate, among others, indicated a large shift in T cell metabolism dependent on oxygen conditions and co-culture interactions, while GSCs are less metabolically responsive to culture conditions. Ongoing experiments will examine precise changes in UDP-GlcNAc and glycosylation precursors in T cells and CAR-T cells via targeted NMR analysis, which we expect will help us understand energy dependent mechanisms of T cell exhaustion and lead to development of novel strategies to sustain T cell function in the hostile TME.